Hydrogenated microstructure and its hydrogenation properties: A density functional theory study - Salam, M.A. (Hindawi Publishing Corporation, 2014)
The relationship between microstructure and hydrogenation properties of the mixed metals has been investigated via different spectroscopic techniques and the density functional theory (DFT). FESEM and TEM analyses demonstrated the nano-grains of Mg2NiH4 and MgH2 on the hydrogenated microstructure of the adsorbents that were confirmed by using XPS analysis technique. SAED pattern of hydrogenated metals attributed the polycrystalline nature of mixed metals and ensured the hydrogenation to Mg2NiH4 and MgH2 compounds. Flower-like rough surface of mixed metals showed high hydrogenation capacity. The density functional theory (DFT) predicted hydrogenation properties; enthalpy and entropy changes of hydrogenated microstructure of MgH2 and Mg2NiH4 are -62.90 kJ/mol, -158 J/mol·K and -52.78 kJ/mol, -166 J/mol·K, respectively. The investigation corresponds to the hydrogen adsorption feasibility, reversible range hydrogenation thermodynamics, and hydrogen desorption energy of 54.72 kJ/mol. DFT predicted IR band for MgH2 and Mg2NiH4 attributed hydrogen saturation on metal surfaces. © 2014 M. Abdus Salam et al.